A case report of dipyridamole stress-induced ST depression progressing to ST-elevation myocardial infarction despite intravenous aminophylline: steal, spasm, or something else?. Issue 2 (26th April 2019) - Li, Ki Fung Cliff; Ho, Hee Hwa; Yew, Min Sen
Abstract: Background: Dipyridamole stress is commonly used for myocardial perfusion imaging and is generally safe. Myocardial ischaemia can occasionally occur and is classically thought to be due to coronary steal as a result of redistribution of flow away from collateral dependent myocardium. Although ischaemia more commonly presents as electrocardiographic (ECG) ST depression and angina, ST-elevation myocardial infarction may occur as a very rare complication. Case summary: We report a case of a patient who developed chest pain and ST depression during dipyridamole infusion. The pain persisted despite intravenous aminophylline with new inferior ST elevation soon after. Coronary angiography showed subtotal right coronary artery occlusion with no collateral supply. The symptoms and ECG changes resolved after percutaneous coronary intervention. Discussion: Coronary steal may not fully account for our patient's presentation given the failure of aminophylline and absent angiographic collaterals. Vasospasm may be triggered by dipyridamole and can directly cause ischaemia or provoke rupture of an unstable plaque. Augmentation of cardiac energetics during vasodilator stress may also play a role.